Knowledge, attitude and practise regarding Mosquito borne diseases in urban and rural areas of Maval, Western Maharashtra - Khot, Farhat Abu; Pandey, Aastha Narayan; Raje, Swati Sanjeev; Kumre, Vishwambhar Kozdev; Memon, Afzal Shakil; Muthiyan, Rhea Sushil (Indian Journal of Community Health, 2024)
Background: Mosquito-borne diseases, have always been a serious health concern in South East Asian countries, particularly India. Maharashtra was reported as one of the highly endemic areas in India and recorded the second-highest number of deaths due to Dengue. The comprehensive management of mosquito-borne diseases hinges not solely on the efforts of health authorities but also on the community's understanding, mindset, and proactive approach in pursuing timely treatment. Aim & Objective: To assess and compare knowledge, attitude and practices of people residing in both the strata regarding Mosquito borne diseases. Methods and Material: A comparative analysis was undertaken in the Maval region, encompassing both rural and urban settings, through a cross-sectional study. Taluka. A sample size of 250 houses—125 houses in each stratum were surveyed. Data collection involved interviews with head of family or next available person. Statistical analysis used: Microsoft excel was used for chi quare and z value. Results: Awareness regarding Mosquito borne disease was 87.2% in urban population and 73.6% in rural population. Conclusions: There are gaps in understanding the timing of Mosquito bites and the identification of breeding sites. This underscores the need for improved knowledge and awareness, with focus on Mosquito control measures to effectively combat these diseases.